Two-dimensional and Doppler echocardiography in the diagnosis of absent pulmonary valve syndrome (surgery without catheterization) - Özkutlu, Süheyla; Özme, Şencan; Atalay, Semra; Saraçlar, Muhsin; Bilgiç, Arman; Yurdakul, Yurdakul (The Turkish Journal of Pediatrics, 1992)
The majority of severely affected infants with absent pulmonary valve syndrome develop varying degrees of respiratory distress. Cardiac catheterization and angiocardiography are still performed in the diagnosis of these infants prior to surgery. However, considering the high risks of these invasive investigations for severely symptomatic infants, diagnosis using only noninvasive methods becomes important. In this regard, we present three cases of absent pulmonary valve syndrome, diagnosed pre-operatively by both two-dimensional and Doppler echocardiography. The diagnosis was confirmed by cardiac catheterization and angiocardiography in two cases and by surgery in a symptomatic infant. Therefore, we are of the opinion that the two-dimensional and Doppler echocardiographic methods are most reliable in diagnosing absent pulmonary valve syndrome, and that severely symptomatic infants can be referred for surgery without catheterization.